Case Report: C-reactive protein apheresis in non-ST-elevation ACS—case series from the C-reactive protein apheresis in Acute Myocardial Infarction Registry - Torzewski, J.; Mattecka, S.; Esposito, F.; Heigl, F.; Fiedler, J.; Sheriff, A. (Frontiers in Cardiovascular Medicine, 2024)
C-reactive protein (CRP) apheresis has been introduced in ST-elevation myocardial infarction and cardiogenic shock. Here, we describe first-in-man application in non-ST-elevation ACS (NSTE-ACS). Seven NSTE-ACS patients with high CRP levels (14.2 mg/L - 154 mg/L) were treated with CRP apheresis. Treatment was well-tolerated. Patients were discharged in good clinical condition.